The EU-UNDP partnership and added value in EU development cooperation - Erik Lundsgaarde (Deutsches Institut für Entwicklungspolitik (DIE), 2021)
European Union (EU) funding for United Nations (UN) organisations has expanded significantly over the last two decades. The EU's partnership with the United Nations Development Programme (UNDP) is an important example of EU-UN cooperation, and UNDP was the fourth-largest UN recipient of European Commission funds in 2018. Against the backdrop of UN and EU reforms that aim to strengthen multilateralism and promote more integrated development cooperation approaches, this paper outlines priority areas in EU-UNDP cooperation and modes of cooperation. The term 'added value' provides an entry point for identifying the rationales for EU funding to UNDP. In EU budgetary discussions, added value is a concept used to inform decisions such as whether to take action at the EU or member state levels or which means of implementation to select. These choices extend to the development cooperation arena, where the term relates to the division of labour agenda and features in assessments of effectiveness. The paper explores three perspectives to consider the added value of funding choices within the EU-UNDP partnership relating to the division of labour between EU institutions and member states, the characteristics of UNDP as an implementation channel and the qualities of the EU as a funder. On the first dimension, the large scale of EU funding for UNDP sets it apart from most member states, though EU funding priorities display elements of specialisation as well as similar emphases to member states. On the second dimension, UNDP's large scope of work, its implementation capacities and accountability standards are attractive to the EU, but additional criteria - including organisational cost effectiveness - can alter the perception of added value. Finally, the scale of EU funding and the possibility to engage in difficult country contexts are key elements of the added value of the EU as a funder. However, the EU's non-core funding emphasis presents a challenge for the UN resource mobilisation agenda calling for greater flexibility in organisational funding. Attention to these multiple dimensions of added value can inform future EU choices on how to orient engagement with UNDP to reinforce strengths of the organisation and enable adaptations envisaged in UN reform processes.
Keywords: 330; Entwicklungshilfe; Entwicklungsplanung; Internationale Zusammenarbeit; Entwicklungsorganisation; EU-Staaten